Nasionalisme dan Negara Bangsa - Cornelis Lay (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
Current issues and challenges have placed nationalism into a dificult position. This leads to the dichotomy oftribalism and globalism or between fragmentation and integration. In Indonesia, the difficult position of nationalism may result from the view that nationalism is equal to a political stream, is interpreted internally, is applied to various interests and means anti-foreign investment. This arcticle discusses the requirements to use civil administration and self-conscious patriotism for understanding nationalism.